Remediation of coal ash and slag disposal site: Comparison of radiological risk assessments (Rudarsko-geološko-naftni zbornik, 2023)
Residuals from coal combustion are known as a potential source of radiation exposure, especially in cases where the coal used in the combustion is characterized by increased radioactivity, resulting in coal ash and slag with potentially high activity concentration of radionuclides. This paper presents the results of the radiological risk assessments based on the ERICA Tool approach, used to estimate dose rates to terrestrial biota in the proximity of a coal fired thermal power plant in Croatia. The study consists of three radiological risk assessments using environmental data on activity concentration (Bqkg-1) from samples collected prior to the remediation of the disposal site and samples after the remediation implementation was completed. The resulting total dose rate to biota derived using data prior to the remediation ranged from 3.28 μGyh-1 to 147.68 μGyh-1. Assessment results of total dose rate based on the data from the studied area after remediation ranged from 0.23 μGyh-1 to 18.06 μGyh-1. The results showed that after the remediation only the total dose rate for lichens and bryophytes slightly exceeded ERICA Tool conservative screening value of 10 μGyh-1, which implies that environmental risks in relation to exposure to the disposal site can be considered negligible. The study results confirm the applicability of the ERICA Tool for the assessment of potential radiological impact and the effective remediation implementation at the coal and ash slag disposal site.